Global warming and carbon dioxide through sciences - Florides, Georgios A.; Christodoulides, Paul (My University, 2009)
Increased atmospheric CO2-concentration is widely being considered as the main driving factor that causes the phenomenon of global warming. This paper attempts to shed more light on the role of atmospheric CO2 in relation to temperature-increase and, more generally, in relation to Earth's life through the geological aeons, based on a review-assessment of existing related studies. It is pointed out that there has been a debate on the accuracy of temperature reconstructions as well as on the exact impact that CO2 has on global warming. Moreover, using three independent sets of data (collected from ice-cores and chemistry) we perform a specific regression analysis which concludes that forecasts about the correlation between CO2-concentration and temperature rely heavily on the choice of data used, and one cannot be positive that indeed such a correlation exists (for chemistry data) or even, if existing (for ice-cores data), whether it leads to a “severe” or a “gentle” global warming. A very recent development on the greenhouse phenomenon is a validated adiabatic model, based on laws of physics, forecasting a maximum temperature-increase of 0.01–0.03 °C for a value doubling the present concentration of atmospheric CO2. Through a further review of related studies and facts from disciplines like biology and geology, where CO2-change is viewed from a different perspective, it is suggested that CO2-change is not necessarily always a negative factor for the environment. In fact it is shown that CO2-increase has stimulated the growth of plants, while the CO2-change history has altered the physiology of plants. Moreover, data from palaeoclimatology show that the CO2-content in the atmosphere is at a minimum in this geological aeon. Finally it is stressed that the understanding of the functioning of Earth's complex climate system (especially for water, solar radiation and so forth) is still poor and, hence, scientific knowledge is not at a level to give definite and precise answers for the causes of global warming.
Keywords: Carbon dioxide; Global warming; Palaeoclimate; Greenhouse gas